2002
DOI: 10.2214/ajr.178.6.1781411
|View full text |Cite
|
Sign up to set email alerts
|

MR Elastography of Breast Cancer: Preliminary Results

Abstract: The results confirm the hypothesis that the prototypic breast MR elastographic technique can quantitatively depict the elastic properties of breast tissues in vivo and reveal high shear elasticity in known breast tumors. Further research is needed to evaluate the potential applications of MR elastography, such as detecting breast carcinoma and characterizing suspicious breast lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
253
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 346 publications
(268 citation statements)
references
References 26 publications
10
253
0
5
Order By: Relevance
“…All of these steps in processing can be applied automatically, without human intervention, to yield quantitative images of tissue shear stiffness, in units of kilopascals. We have used the designation "shear stiffness", rather than "shear modulus" to indicate that the measurements may include a viscous component, although this is likely to be very small at the low driving frequency used (22). The elastograms were analyzed by measuring mean shear stiffness within a large, manually specified region-of interest that included an entire cross-sectional image of hepatic parenchyma, while excluding major blood vessels, such as hepatic veins, main portal veins and branches that have width greater than 6 pixels (about 8 mm).…”
Section: Mr Elastogramsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these steps in processing can be applied automatically, without human intervention, to yield quantitative images of tissue shear stiffness, in units of kilopascals. We have used the designation "shear stiffness", rather than "shear modulus" to indicate that the measurements may include a viscous component, although this is likely to be very small at the low driving frequency used (22). The elastograms were analyzed by measuring mean shear stiffness within a large, manually specified region-of interest that included an entire cross-sectional image of hepatic parenchyma, while excluding major blood vessels, such as hepatic veins, main portal veins and branches that have width greater than 6 pixels (about 8 mm).…”
Section: Mr Elastogramsmentioning
confidence: 99%
“…MR Elastography can be readily implemented on standard MR imaging systems with little additional hardware (21). To date, MR Elastography has been applied to quantitatively assess the viscoelastic properties of many human tissues in vivo, including breast, brain, muscle, and liver (22)(23)(24)(25)(26)(27)(28)(29). Preliminary studies in human subjects have confirmed the feasibility and promise of this technique for the quantitative assessment of hepatic fibrosis (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19] In MRE, the sample is excited mechanically, and the response is measured with magnetic resonance imaging. The primary goal of the technique is early detection of tissue lesions by determining the elasticity coefficients from the wavelengths of the stress waves.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic Resonance Elastography (MRE) can directly visualise and measure tissue elasticity [5][6][7][8], and has been applied to resolve stiffness characteristics of a variety human tissues and organs, such as muscle [9][10][11][12], breast [13][14][15][16][17], liver [18][19][20] and the brain [21][22][23][24][25][26][27][28][29]. MRE acquisition requires application of mechanical waves to tissue within the MRI, phase-contrast MR pulse sequence extended with motion encoding gradient (MEGs), and sophisticated inverse problem methods to identify an elastic modulus map of the tissue.…”
Section: Introductionmentioning
confidence: 99%